2014
DOI: 10.1063/1.4878739
|View full text |Cite
|
Sign up to set email alerts
|

Multiple double-metal bias-free terahertz emitters

Abstract: We demonstrate multiplexed terahertz emitters that exhibits 2 THz bandwidth that do not require an external bias. The emitters operate under uniform illumination eliminating the need for a micro-lens array and are fabricated with periodic Au and Pb structures on GaAs. Terahertz emission originates from the lateral photo-Dember effect and from the different Schottky barrier heights of the chosen metal pair. We characterize the emitters and determine that most terahertz emission at 300 K is due to band-bending d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…The same group presented a simple but robust LPD device concept using metal stripes with two different thicknesses, one of which thin enough to be transparent for THz radiation. 13 This arrangement can be easily multiplexed, and the efficiency of this concept has been demonstrated experimentally. Moreover, by choosing mask metals that form different Schottky barrier heights, lateral electric fields can be induced at the emitter surface in which lateral photocurrents can be driven.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same group presented a simple but robust LPD device concept using metal stripes with two different thicknesses, one of which thin enough to be transparent for THz radiation. 13 This arrangement can be easily multiplexed, and the efficiency of this concept has been demonstrated experimentally. Moreover, by choosing mask metals that form different Schottky barrier heights, lateral electric fields can be induced at the emitter surface in which lateral photocurrents can be driven.…”
Section: Introductionmentioning
confidence: 99%
“…10 Recently, lateral photo-Dember (LPD) emitters have been demonstrated, in which the photogenerated electrons move parallel to the semiconductor surface and the generated THz radiation is effectively coupled out. 4,[11][12][13] It has been shown that the efficiency of LPD emitters is comparable to those of PC emitters with the additional advantage of biasfree operation. 11 However, there has been a debate on the physical origin for the strong THz emission from LPD devices.…”
Section: Introductionmentioning
confidence: 99%
“…These emitters come in the form of continuous layers 9,10 or, recently, 11,12 in the form of discontinuous periodic structures where in addition to in-plane Schottky-field induced THz emission, the lateral photo-dember effect plays a role.…”
mentioning
confidence: 99%
“…The substrate material is semi-insulating GaAs. The fabrication and characterization of the emitters is described in [20,21]. Two DM emitters with the above geometry were fabricated for the experiments, one with circular emitter elements to generate radial polarization and one emitter with straight elements that was used for the measurement of angular emission dependence and the focusing experiments.…”
Section: Fabrication Of Emittersmentioning
confidence: 99%
“…This paper explores beam steering using large-area emitters that generate THz radiation via diffusion currents, also known as the lateral photo-Dember (LPD) effect [17][18][19] and Schottky potentials [20,21]. LPD and Schottky potential-based double metallic emitters have been found to have similar spectral bandwidth with photo-conductive emitters [19,20] . Various THz sources have been assessed for their capability to be implemented in a phase-delay array, but in-depth studies of a scheme using LPD emitters has yet to be tested.…”
mentioning
confidence: 99%